The Relationship between the Food Nutritional Value and the Absence of Microbial Hazards - Shaltout, Fahim A. (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2024)
Meat is a valuable element of the human diet as it contains essential elements such as protein, vitamins, and minerals. However, these foods are also vulnerable to microbial pathogens and spoilage, posing significant risks to human health. Ionizing radiation is used in food irradiation to maintain the safety and quality of the food items, specifically beef. For decades, food irradiation has been used to reduce microbial contamination and extend the storage period. The procedure entails subjecting the food item to a regulated amount of ionizing radiation, usually accomplished by applying gamma rays, electron beams, or X-rays. The radiation disrupts the DNA and other cellular components of microbes, making them unable to reproduce and causing their death. The procedure also breaks down some of the molecules in the food product, which can affect its nutritional quality and sensory properties.